QUR’ANIC CONCEPTS OF MAN AND NATURE AND THEIR ETHICAL IMPLICATIONS FOR HUMAN BEHAVIOR: DEVELOPING AN ALTERNATIVE ISLAMIC FRAMEWORK - Furqani, Hafas; Haneef, Mohamed Aslam (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2016)
The question of ethics in economic development has taken centre stage in recent years. The recurring financial crises and the devastation of the environment provide opportunities to revisit the issue of re-introducing ethics into economics. Even in mainstream academic discourse, global scholarship is searching for appropriate ethical foundations to be the basis of human behavior in dealing with nature while at the same time enabling man to enjoy maximum well-being. Mainstream neoclassical economics is criticized for not having a holistic perspective that would be the basis of genuine sustainable development. This criticism emanates primarily from the microfoundations of neoclassical economics that idealize individual rationality within a framework that glorifies self-interest/selfish behavior and utility maximization postulates. In this paper, we attempt to investigate the Islamic perspective on the relationship of man and nature, vis-a-vis the framework of an ethics-based approach to development. A new micro-foundational framework of the man-nature relationship will be presented. This paper attempts to develop outlines of the conceptual framework based on selected Qur’anic concepts that represent the moral foundations of Islam, which require the individual to attain taqwa (piety) and full consciousness of huquq (rights and obligations) vis-à-vis oneself, others and nature while being motivated to maximize maslahah (benefit) and avoid mafsadah (harm) to oneself, society and nature. The intended goal is to attain self-betterment/realization that incorporates spiritual transformation. We argue that in this proposed conceptual framework man and nature are recognized as having mutual co-existence, whereby one cannot exist without the other, and the well-being of one depends on the well-being of the other. This will provide balance and harmony to better achieve sustainable development.